Beyond the discourses of rating. When reception matters more than consumption. An empirical study about the Colombian television audience - Arango-Forero, Germán; Gómez-Giraldo, Juan Carlos; Hernández-Rodríguez, Juan Camilo (Estudios sobre el Mensaje Periodístico, 2014)
Rating measurement’ industrial system faces challenges and limits due to new consumption habits and particular content preferences among audiences, in a television environment characterized by globalization, oversupply, thematic programming and audiences’ fragmentation. This research article shows the main results obtained from a quantitative study, of a probabilistic sample, financed by RCN channel, applied to Colombian T.V. audiences, between 17 and 60, who live in the 12 most important urban areas.